2009
DOI: 10.1097/meg.0b013e328326f598
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of immigration status, race and language barriers on chronic hepatitis C virus infection management and treatment outcomes

Abstract: In the context of a multidisciplinary, multilingual universal health care system, by studying the influence of barriers to HCV investigation and successful therapy can be abrogated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 25 publications
3
14
0
Order By: Relevance
“…For example, in a quantitative study of health care services access specific to hepatitis C virus treatment, Giordano et al [11] employed secondary data and found no difference between immigrants and non-immigrants. However, rate of access was determined by comparing hepatitis C treatment initiation rates for immigrants versus non-immigrants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in a quantitative study of health care services access specific to hepatitis C virus treatment, Giordano et al [11] employed secondary data and found no difference between immigrants and non-immigrants. However, rate of access was determined by comparing hepatitis C treatment initiation rates for immigrants versus non-immigrants.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, six studies analyzed secondary data and four analyzed primary data. Most studies that analyzed secondary data sought to determine whether or not immigrants and nonimmigrants experienced different rates of access to health care [11][12][13][14]. With the exception of access to cervical cancer screening [15], secondary data analyses revealed no difference in health care access between immigrants and non-immigrants.…”
Section: Trends In Quantitative and Qualitative Studiesmentioning
confidence: 99%
“…Pre- and post-HCV test counselling has been identified as an area requiring skills development [42,105], and there is a need for physicians to be responsive to patients’ reports of adverse treatment effects [72]. An obstacle to communication that has received little attention to date is language barriers between some immigrants and minority ethnic groups and their HCV treatment providers [61,106]. …”
Section: Social Level Factorsmentioning
confidence: 99%
“…One Italian study showed that immigrants were significantly less likely than Italian-born patients to receive HBV antiviral therapy [76]. However, other studies have shown no difference in treatment uptake rates among immigrants [79]. Lack of insurance coverage [34] and lack of access to specialist physicians [78] were felt to be barriers to treatment in some studies.…”
Section: Improving Case Identification and Treatment Among Migrantsmentioning
confidence: 99%